Conserved Patterns of Symmetric Inversion in the Genome Evolution of Bordetella Respiratory Pathogens - Michael R. Weigand; Yanhui Peng; Dhwani Batra; Mark Burroughs; Jamie K. Davis; Kristen Knipe; Vladimir N. Loparev; Taccara Johnson; Phalasy Juieng; Lori A. Rowe; Mili Sheth; Kevin Tang; et al. (mSystems, 2019)
ABSTRACT Whooping cough (pertussis), primarily caused by Bordetella pertussis, has resurged in the United States, and circulating strains exhibit considerable chromosome structural fluidity in the form of rearrangement and deletion. The genus Bordetella includes additional pathogenic species infecting various animals, some even causing pertussis-like respiratory disease in humans; however, investigation of their genome evolution has been limited. We studied chromosome structure in complete genome sequences from 167 Bordetella species isolates, as well as 469 B. pertussis isolates, to gain a generalized understanding of rearrangement patterns among these related pathogens. Observed changes in gene order primarily resulted from large inversions and were only detected in species with genomes harboring multicopy insertion sequence (IS) elements, most notably B. holmesii and B. parapertussis. While genomes of B. pertussis contain >240 copies of IS481, IS elements appear less numerous in other species and yield less chromosome structural diversity through rearrangement. These data were further used to predict all possible rearrangements between IS element copies present in Bordetella genomes, revealing that only a subset is observed among circulating strains. Therefore, while it appears that rearrangement occurs less frequently in other species than in B. pertussis, these clinically relevant respiratory pathogens likely experience similar mutation of gene order. The resulting chromosome structural fluidity presents both challenges and opportunity for the study of Bordetella respiratory pathogens. IMPORTANCE Bordetella pertussis is the primary agent of whooping cough (pertussis). The Bordetella genus includes additional pathogens of animals and humans, including some that cause pertussis-like respiratory illness. The chromosome of B. pertussis has previously been shown to exhibit considerable structural rearrangement, but insufficient data have prevented comparable investigation in related species. In this study, we analyze chromosome structure variation in several Bordetella species to gain a generalized understanding of rearrangement patterns in this genus. Just as in B. pertussis, we observed inversions in other species that likely result from common mutational processes. We used these data to further predict additional, unobserved inversions, suggesting that specific genome structures may be preferred in each species.